Model Dinamik sebagai Upaya Pencapaian Sinkronisasi Nitrogen pada Budidaya Selada dengan Pupuk Hijau Paitan - Yuni Agung Nugroho; Elik Murni Ningtyas Ningsih (JOURNAL OF TROPICAL SOILS, 2009)
Dynamic Model as Attainment Effort of Nitrogen Synchronization at Lettuce Cultivation with Green Manure Paitan  (Y.A. Nugroho and E.M.N. Ningsih): Lettuce (Lactuca sativa) is  vegetable crop that consumed part of the leaf and harvested at a phase of vegetative. Nitrogen play important role in growth  at phase of vegetative. Nitrogen in spacious have the character of easy to lose because of leaching.  Increasing yield of  lettuce can be  done  by improving Nitrogen synchronization, that is precisely usage moment with ready moment  of N during and amount of its. The research was aimed to study of  the pattern nitrogen requirement  for lettuce crop, ready pattern of nitrogen by Tithonia diversifolia and design nitrogen synchronization model between lettuce crop with green manure of  T. diversifolia. The research were divided in two phases that are phase research 1: Dynamic modeling for nitrogen synchronization on lettuce cultivation by green manure of T. diversifolia, and phase research 2: Fertilizer technology of high nitrogen synchronization on lettuce cultivation by green manure of T. diversifolia. The result  of phase research 1 (first year research) shows that dynamic model of N requirement by lettuce crop,  release  and availability model of N by T. diversifolia and synchronization model of N  between requirement of N  lettuce with  release and availability of N by T. diversifolia.   The dynamic model   indicate that   giving  10 t ha-1  of  T. diversifolia which given 2 weeks before transplanting at lettuce crop can support high result and growth because happened good synchronization of N.